Inhibitory effect of kanamycin on in vitro culture of Lycopersicon esculentum Mill cv. Mt11. - A.R., Siti Suhaila; Mohd. Saleh, Norihan (Universiti Darul Iman Malaysia, 2010)
Excised cotyledons of tomato (Lycopersicon esculentum Mill cv. MT11) were cultured on selective medium containing kanamycin at various concentrations (50, 100, 200, 300 mg/L). Significant toxic effects were observed when the cotyledon explants were grown on MS medium supplemented with 5mg/L kinetin and 100 mg/L kanamycin. The regeneration of callus was decreased as the concentration of kanamycin increased from 200 to 300 mg/L. Explants grown on MS medium supplemented with 5mg/L kinetin and 50 mg/L kanamycin showed the least toxic effects (mean survival rate 48.0% ± 0.19) compared to the rest of the concentrations tested. Even though 100 mg/L of kanamycin allows the non-transformed explants to grow on the medium, the shoot primordia would not develop further.The result suggests that 100 mg/L of kanamycin can be used effectively to differentiate between non-transformed and transformed MT11 tomato explants with a death rate of more than 82% of non-transformed explants, after 4 weeks of incubation on selection medium. Therefore, 100 mg/L kanamycin is suitable for minimal inhibition concentration for MT11 and true transformants can be selected at this concentration for the transformation system.